The Effect of Bladder Point 23 Acupressure Therapy on Back Pain Intensity in Pregnant Women in the Thirty Trimester - Citra Dondo; Rifzul Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Back pain is one of the common complaints experienced by pregnant women, especially in the third trimester. According to data from the World Health Organization (WHO), around 50-70% of pregnant women experience back pain which can affect their quality of life (WHO, 2021). Acupressure therapy, especially at the Blader 23 point, has been known as a non-pharmacological method that can reduce pain. This study aims to analyze the effect of acupressure therapy at the Blader 23 point on the intensity of back pain in pregnant women in the third trimester. Research Methods: The research method used in this study was a pre-experiment with a pre-post group test. The study sample consisted of 20 primigravida pregnant women. Pain intensity was measured using a numeric scale (NRS) before and after the intervention. The data obtained were analyzed using a paired t-test. There was a significant difference in the level of pain in pregnant women in the third trimester between before and after being given acupressure at the Blader 23 point, this was evidenced by the mean value of the pre-test results of 25.5 but the mean value of the post-test results was 23.2. This is reinforced by the results of the t-test obtained t count 7.254. Furthermore, based on the results of the calculation of the level of significance, it shows that the value of